The Role of Libraries in Community Empowerment: A Systematic Review - Mubofu, Christian; Mambo, Henry (Department Library of Governance Institut of Home Affairs, 2021)
Problem Statement: Libraries as public information agencies act as catalysts that provide reliable information that empowers people in making the right decision in terms of development plans put forward by various sectors. However, studies on how and where the society, access, and the use of relevant information that empower them to contribute positively in these sectors are inadequately reported in scholarly literatures. Purpose: This study in particular reports the role of libraries in community empowerment and the challenges faced by libraries in the dissemination of information for community empowerment. Method: This study is a scoping and a literature review of the role of libraries in community empowerment. The study adopted Arksey and O’ Malley framework. Google scholar, JSTOR, Ebscohost, Emerald insight, fullfreepdf, Eric, Research4life databases, and Taylor & Francis were used as the main sources of information. Results: The result revealed that libraries provide free internet access and information resources. Libraries also act as information acquisition centre, community empowerment programs as well as a centre for building capacity, and learning support. The study also revealed that job dissatisfaction among library staff, inadequate facilities, lack of commitment, lack of teamwork and poor relationships among staff, insufficient knowledge and skills among library staff are some of the challenges libraries have to face as an effective provision of information services. Conclusion: The study concludes that there are countless and well established role of libraries in community empowerment in various sectors like education, health, agriculture and technology. Libraries are the main centre for information that contributes greatly to community empowerment through building capacity and learning support. Keywords: Libraries; Empowerment; Community Empowerment; Role of Libraries